Tribute to Horst R. Thieme on the occasion of his 60th birthday - Hal L. Smith (Mathematical Biosciences and Engineering)
It is a great pleasure to congratulate Horst on his 60th birthdayand to dedicate this volume to him in honor of his manycontributions to the field of mathematical biology.   Horst Thieme has been, over a period of thirty years, one of themost productive scientists in Mathematical Biology, with numerousworks on subjects centered on population biology and transmissionand control of infectious disease. He has provided a number ofrigorous mathematical tools for the study of structured populations,the problem of biological invasion, and the limiting behavior ofepidemic and other population models. Horst Thieme's work can becharacterized by deep insight into the underlying structure ofbiological phenomena and mechanisms, great skills in entering theseinsights into feasible models, and by rigorous mathematicsvalidating or sometimes rejecting modeling approaches.For more information please click the “Full Text” above.